The influence of the pedagogical model on psychological variables in 1st year students from ESTSP-IPP - Teixeira, Ricardo J. (2013)
Introduction – Adapting to Higher Education is filled with academic experiences that might be stressful for students. The new pedagogical models brought about by the Bologna process put into play new variables that are important to look at, namely in terms of health. This research aims to analyze associations between the pedagogical model (Problem Based Learning vs more traditional approaches) and psychological variables (coping, emotional deregulations, psychosomatic symptoms, perceived stress, and affect). Method – This study has a cross-sectional design. The following online questionnaires were used: Brief-COPE, Difficulties in Emotion Regulation Scale, Perceived Stress Scale, Manifestations of Physical Discomfort Questionnaire, and Positive and Negative Affect Schedule. The sample consisted of 183 first-year students (84% female) from the School of Allied Health Sciences – Polytechnic Institute of Porto. Results – Significant correlations between demographic and psychological variables were found. Considering different pedagogical models, significant differences in psychological variables were found. The main predictors of stress in the sample were: being female, inclusion in the PBL model, higher indexes of emotional deregulation, more psychosomatic symptoms, lower positive affect, and higher negative affect. Conclusion – Differences between pedagogical models are discussed while reflecting on practical implications and suggestions for future research.